INFLUENCE OF PLAYGROUP ON THE DEVELOPMENT OF CHILDREN AGED 4-6 YEARS OF WORKING MOTHERS (A RETROSPECTIVE COHORT STUDY AT A PRIVATE KINDERGARTEN, KUPANG) - AGUSTINA INA (Research and Community Service Unit, Politeknik Kesehatan Kemenkes Kupang, 2014)
Early childhood is a period very sensitive to the environment. This period is referred as the golden age of children's development, the window of opportunity, and the critical time. Appropriate stimulus and good nutrition during this time is important for the child's growth and development in the future. One alternative to develop child's potential is the early childhood education, among which is the playgroup. This study was an observational analytic study with a retrospective cohort design. The study was conducted from April to June 2013. The data were collected using prescreening developmental questionnaires and observation. Sample consisted of 23 kindergarten children from playgroup whose mothers worked and control groups consisted of 23 kindergarten children not from playgroup whose mothers worked. The results of this study were presented descriptively. All kindergarten children not from playgroup had normal development, while from those not from the playgroup, 10 (43.5%) had abnormal development. However, this difference only applied to the sample and could not be generalized because the result of inferential statistical showed that playgroup had no effect on the development of children with p = 0.998. In conclusion, Playgroup does not affect child's development. However, children attending playgroup has potential to undergo normal development than those not attending playgroup. To analyze the influence of playgroup, it is suggested to undertake further study on the influence of play group on the development of pre-kindergarten.